Volume 4B: Combustion, Fuels and Emissions 2017
DOI: 10.1115/gt2017-64691
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PVC Dynamics on Shear Layer Response in a Swirling Jet

Abstract: Combustion instability, or the coupling between flame heat release rate oscillations and combustor acoustics, is a significant issue in the operation of gas turbine combustors. This coupling is often driven by oscillations in the flow field. Shear layer roll-up, in particular, has been shown to drive longitudinal combustion instability in a number of systems, including both laboratory and industrial combustors. One method for suppressing combustion instability would be to suppress the receptivity of the shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…. Frederick et al 19 showed in their analysis that the PVC leads to a thickening of the shear layers and, hence, reduces the growth rate of the Kelvin-Helmholtz instability, which is also known as a key driver for thermoacoustic instability. 52 .…”
Section: Interaction Of a Thermoacoustic Instability And The Pvc In Amentioning
confidence: 99%
See 2 more Smart Citations
“…. Frederick et al 19 showed in their analysis that the PVC leads to a thickening of the shear layers and, hence, reduces the growth rate of the Kelvin-Helmholtz instability, which is also known as a key driver for thermoacoustic instability. 52 .…”
Section: Interaction Of a Thermoacoustic Instability And The Pvc In Amentioning
confidence: 99%
“…The present experiment reveals a significant suppression of the thermoacoustic instability through the actuation of the PVC. An explanation for the suppression of the thermoacoustic instability by the PVC is given by Frederick et al, 19 as described above. However, our experiments conducted at perfectly premixed conditions for different actuation frequencies and amplitudes (compare Figures 10 and 11) do not support this explanation.…”
Section: Interaction Of a Thermoacoustic Instability And The Pvc In Amentioning
confidence: 99%
See 1 more Smart Citation